Development of phosphate coating on the surface of TMT rebar: an option to study the effect of n-SiO2 as an additive. (21st October 2017) - Manna, M.; Shah, A.; Kulkarni, S. V.
Abstract : Phosphate conversion coatings on the rebar surfaces with oxide scale (OS) and without oxide scale (WOS) have been tried with or without addition of n-silica particles as an additive to check the effect of n-silica on phosphating behaviour of rebar. All the phosphate coatings were characterised using SEM–EDS, XRD, Tafel, EIS, salt spray and pull out test. Hopeite was identified as major zinc phosphate phase in the coating which was obtained on the OS steel surface, whereas hopeite along with spencerite compounds were identified as major zinc phosphate compounds present in the coating which was obtained on the WOS steel surface. Thicker phosphate coatings were obtained when WOS and OS rebars were treated in n-silica-added and n-silica-free phosphating solution, respectively, and vice versa. Nano-silica acts as a catalyst in the formation of more dense and compact phosphate coating on the surface of WOS rebar, whereas nano-silica acts as a poison for phosphating reaction on the surface of OS rebar. Smoother phosphate coatings were obtained on both types of rebar surfaces when treatment was done in silica-added phosphate solution. Silica acts as a levelling agent for phosphate coating on both the steel surfaces. Phosphate coatings showed better resistance against red rust formation when OS rebar was treated in n-silica-free phosphate solution and WOS rebar was treated in n-silica-added phosphate solution. These two phosphate-coated OS and WOS steel substrates produced 29 and 11% increment in bond strength with the concrete structure compared to uncoated steel substrate, respectively.